Enhancing Thermal Conductivity and Heat Transfer Performance with Nanocellulose-Based Nanofluids: A Comprehensive Study - Aqeel A.A.K.A.; Hajjaj S.S.H.; Mohamed H.; Obeidat F.S. (Springer Science and Business Media Deutschland GmbH, 2025)
This article investigates how nanocellulose might improve heat transmission by creating and analyzing nanofluids. Interest has been sparked by the improved thermal properties of nanofluids, which are made up of nanoparticles scattered throughout base fluids. In this work, nanofluids with various volume concentrations of cellulose nanocrystals (CNC) are made by dispersing the CNC in distilled water and ethylene glycol. Stirring and ultrasonication are used to guarantee stability throughout the preparation process. Thermal conductivity experiments show that the presence of CNC nanoparticles significantly increases thermal conductivity, indicating a proportionate connection between volume concentration and temperature. According to density measurements, temperature and volume concentration affect nanofluid density, with more significant concentrations and lower temperatures resulting in greater density. Overall, this study demonstrates the potential of nanofluids based on nanocellulose to improve heat transmission while revealing essential details about their production, stability, and thermal characteristics. These discoveries substantially influence environmental science, medicine, and materials engineering. They also offer opportunities for improved thermal management systems. ? The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.